Biopetrol Production from Acids in Palm Oil Waste - Syaiful Nizam, Hassan; Anis Farina, Mansor; Aizil Haikal, Omar (Universiti Malaysia Pahang, 2008)

(untitled)
Biopetrol is the alternative fuel derived from vegetable oil which has similar properties with petrol. The increasing petrol price, the decrease of petrol supply and the biodiesel production from vegetable oils are the reasons why biopetrol should be produced for petrol-used vehicles. The studies on the producing of biopetrol from acids in palm oil waste will be carried out to expand the usefulness of the oil palm waste. Acids consists 55% to 65% of the crude palm oil component. In this experiment, palmitic and oleic acids, those presenting in palm oil waste will be used as research materials. All acids in palm oil waste are fatty acids, the subset of carboxylic acids. There are two processes to be undergone: In converting the acids into isooctane, the main component of petrol and biopetrol, heating and distilling acids at isooctane's boiling point through batch thermal cracking process in laboratory scale. The resulted organic liquid then will be analyzed and compared with the properties of isooctane by using gas chromatography (GC) analysis. Gas chromatography results showed that C8H18 presents in the mixture of the heated liquid. These findings proved that oil palm waste can be converted into biopetrol, and biopetrol can be produced to overcome the problem of supplying petrol to petrol-used vehicles.